2003
DOI: 10.1016/j.jbi.2003.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Using nurses’ natural language entries to build a concept-oriented terminology for patients’ chief complaints in the emergency department

Abstract: Information about the chief complaint (CC), also known as the patient's reason for seeking emergency care, is critical for patient prioritization for treatment and determination of patient flow through the emergency department (ED). Triage nurses document the CC at the start of the ED visit, and the data are increasingly available in electronic form. Despite the clinical and operational significance of the CC to the ED, there is no standard CC terminology. We propose the construction of concept-oriented nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…Cimino's 1998 “Desiderata” laid out requirements for a sound controlled vocabulary or thesaurus on a general level, applicable to any medical vocabulary. Travers (2003), and Travers & Haas (2003) reported on research that gathered and analyzed a large portion of the information needed to build a thesaurus that would satisfy these requirements, including concept orientation, recognition of synonyms, and means of identifying needed updates and modifications of the thesaurus over time. We have placed others of Cimino's requirements in the specific context of the CC, framing questions relating to scope and coverage (e.g., pre‐ or post‐coordination of concepts, and merging similar concepts), and the structure of the thesaurus (e.g., inclusion and use of MOI and qualifiers and modifiers).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cimino's 1998 “Desiderata” laid out requirements for a sound controlled vocabulary or thesaurus on a general level, applicable to any medical vocabulary. Travers (2003), and Travers & Haas (2003) reported on research that gathered and analyzed a large portion of the information needed to build a thesaurus that would satisfy these requirements, including concept orientation, recognition of synonyms, and means of identifying needed updates and modifications of the thesaurus over time. We have placed others of Cimino's requirements in the specific context of the CC, framing questions relating to scope and coverage (e.g., pre‐ or post‐coordination of concepts, and merging similar concepts), and the structure of the thesaurus (e.g., inclusion and use of MOI and qualifiers and modifiers).…”
Section: Discussionmentioning
confidence: 99%
“…We present a brief overview of Travers' research here; details may be found in her dissertation and related papers (Travers, 2003; Travers & Bodenreider, 2002; Travers & Haas, 2003). She created a corpus of one year's worth of CCs, collected from three southeastern EDs representing urban, rural and suburban academic medical centers.…”
Section: Analysis Of Chief Complaintsmentioning
confidence: 99%
“…In a pilot study, the addition of information from TNs led to improved sensitivity for three syndromes, Respiratory, Fever-Rash and Gastrointestinal, from 17% - 40% to over 81%, while specificity was maintained above 80% [11]. However, use of TNs can also increase the risk of false classification, since they can include syndrome-relevant information in non-standard terms, such as abbreviations, misspellings, negated forms, and other expressions characteristic of free-text notes [15]. …”
Section: Introductionmentioning
confidence: 99%
“…11,12 The current study is part of our ongoing effort to develop a vocabulary standard for ED CCs by using a data-driven approach and the UMLS. 12,13 This approach supports two important goals: to work toward comprehensive coverage of the concepts needed to express CCs and to work toward a concept-oriented vocabulary that allows maximum flexibility in the design of information systems that incorporate it. 11 We began the ongoing project with an analysis of a corpus of ED CC entries, to identify the terms used to describe ED CC concepts.…”
mentioning
confidence: 99%
“…11 We began the ongoing project with an analysis of a corpus of ED CC entries, to identify the terms used to describe ED CC concepts. 13 We then developed a natural language-processing system called Emergency Medical Text Processor (EMT-P), which cleans CC data (e.g., chst pn, chest pai, chert pain) and then maps the processed CCs to standard terms that represent UMLS concepts (e.g., chest pain). EMT-P includes separate modules to address the variability in natural-language CC entries such as acronyms, abbreviations, truncations, and coordinate structures.…”
mentioning
confidence: 99%